Violência contra idosos: rede de proteção e atenção ao idoso - Camargo, Katiane de Quadros Bones (2015)
The study presents the types of violence and institutional violations committed against the elderly in city from Passo Fundo- RS, arising from the survey conducted with the Administrative Procedures brought by the Public Ministry in the years 2012 and 2013 and supplemented with details of the protect net social. The identification of the causes, the characterization of violence and the demographic profile of the elderly and the offender will contribute to the strengthening of public policies. It is a documentary research of observational delimitation, descriptive, retrospective. Information was obtained from the protocols classified by socio-demographic characterization of types and victimization. The information on the record socio-demographic and victimization were classified into categories. The qualitative variables were described by absolute and relative frequency. Such information is entered and stored directly in Microsoft Office Excel 2007 version taking into account the operating rules of this software program. Data were compiled and tabulated in a spreadsheet created by the researcher and presented in tabular form. The research results can contribute to support interdisciplinary strategies and action plans aimed at qualifying public policies on combating violence against the elderly